Oral administration of French maritime pine bark extract (Flavangenol®) improves clinical symptoms in photoaged facial skin - Furumura M; Sato N; Kusaba N; Takagaki K; Nakayama J (Clinical Interventions in Aging, 2012)
Minao Furumura,1,2 Noriko Sato,1 Nobutaka Kusaba,3 Kinya Takagaki,3 Juichiro Nakayama11Department of Dermatology, Fukuoka University School of Medicine, Fukuoka, 2Department of Dermatology, Kurume University School of Medicine and Kurume University Institute of Cutaneous Cell Biology, Fukuoka, 3Toyo Shinyaku Co Ltd, Tosu City, Saga, JapanBackground: French maritime pine bark extract (PBE) has gained popularity as a dietary supplement in the treatment of various diseases due to its polyphenol-rich ingredients. Oligometric proanthocyanidins (OPCs), a class of bioflavonoid complexes, are enriched in French maritime PBE and have antioxidant and anti-inflammatory activity. Previous studies have suggested that French maritime PBE helps reduce ultraviolet radiation damage to the skin and may protect human facial skin from symptoms of photoaging. To evaluate the clinical efficacy of French maritime PBE in the improvement of photodamaged facial skin, we conducted a randomized trial of oral supplementation with PBE.Methods: One hundred and twelve women with mild to moderate photoaging of the skin were randomized to either a 12-week open trial regimen of 100 mg PBE supplementation once daily or to a parallel-group trial regimen of 40 mg PBE supplementation once daily.Results: A significant decrease in clinical grading of skin photoaging scores was observed in both time courses of 100 mg daily and 40 mg daily PBE supplementation regimens. A significant reduction in the pigmentation of age spots was also demonstrated utilizing skin color measurements.Conclusion: Clinically significant improvement in photodamaged skin could be achieved with PBE. Our findings confirm the efficacy and safety of PBE.Keywords: polyphenols, pine bark extract, skin photoaging, antioxidants, antiaging